KOMPARASI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWAPADA MATA PELAJARAN TEKNIK LISTRIK KELAS X TEKNIK AUDIO VIDEO DI SMKN 5 PADANG - Elmizal Elmizal; Thamrin Thamrin; Hanesman Hanesman (Universitas Negeri Padang, 2017)
The problem in this study is the low average learning outcomes of learners on the subjects of Electrical Engineering is under the Learning Completeness (KB) which has been established SMKN 5 Padang is 75. There are 48.15% 1E1, 61.29 1E2 and 65.62% 1E3. This study aims to determine the comparative application of cooperative learning model type Think Pair Share and Problem Based Learning on student learning outcomes on the subjects Electrical Engineering class X Audio Video Technique at SMKN 5 Padang. The type of this research is experimental design with intact grup comparison design. The sample of this research is 1E1 A class as experiment class I using Think Pair Share and class 1E3 B as experiment class II using Problem Based Learning model. Data collection techniques were obtained from post-test in experimental class I and II, than analyzed for homogeneity test, normality test and hypothesis test. This research results the average value of students using cooperative learning model Think Pair Share type (80,27) is higher then using Problem Based Learning model that is (74,13). The result of hypotehesis calculation at significant level α = 0,05, obtained t count > t table that is 2,580> 2,045, because tcount is bigger than ttable, hil n hypothesis (Ho) rejected and alternative hypothesis (Ha) accepted. Keywords: Think Pair Share model, Problem Based Learning model, Experimental, Learning Outcomes, Experiments.